2012
DOI: 10.1002/pbc.24412
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c‐FLIP in pulmonary metastases in osteosarcoma patients and human xenografts

Abstract: Objective(s) We have previously shown that Fas expression inversely correlates with the metastatic potential of osteosarcoma (OS) to the lung. FasL is constitutively expressed in the lung microenvironment and eliminates Fas+ osteosarcoma cells leaving Fas− cells to form metastases. Absence of FasL in the lung epithelium or blocking the Fas-signaling pathway interfered with this clearance mechanism allowing Fas+ cells to remain and form lung metastases. We also demonstrated that while the majority of patient OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Many anti-apoptotic proteins such as C-FLIP, MCL-1, and XIAP inhibit apoptosis through disruption of extrinsic/intrinsic apoptotic pathways in cancers [33]. C-FLIP inhibits FAS-mediated apoptosis through suppression of caspase-8 activation [34]. MCL-1 blocks intrinsic apoptotic signaling transduction through preventing the loss of mitochondrial membrane potential and cytochrome-c release from mitochondria [35].…”
Section: Discussionmentioning
confidence: 99%
“…Many anti-apoptotic proteins such as C-FLIP, MCL-1, and XIAP inhibit apoptosis through disruption of extrinsic/intrinsic apoptotic pathways in cancers [33]. C-FLIP inhibits FAS-mediated apoptosis through suppression of caspase-8 activation [34]. MCL-1 blocks intrinsic apoptotic signaling transduction through preventing the loss of mitochondrial membrane potential and cytochrome-c release from mitochondria [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that thatezrin, a member of the ezrin-radixin-moesin family, is highly expressed in metastatic OS cell lines, and is required for OS metastasis, due to its functional connection with the actin cytoskeleton ( 7 ). In addition, the expression of Fas has previously been associated with OS metastasis, and an inhibitor of the Fas pathway (c-FLIP) has been developed as a potential treatment for patients with lung metastasis ( 8 ). Nagao-Kitamoto et al ( 9 ) demonstrated that knockdown of GLI family zinc finger 2 (GLI2) using RNA interference was able to significantly attenuate the migration and invasion of OS cells; thus suggesting that inhibition of GLI2 may be a potential strategy for the treatment of patients with metastatic OS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to support resistance of cell death, c-FLIP triggers both epithelial-mesenchymal transition (EMT) and motility of cancer cells, thus promoting tumor invasive potential. Therefore, it is unsurprising that high levels of c-FLIP has been reported in several cancer settings such as colorectal cancer ( 46 ), cervical cancer ( 47 ), pancreatic cancer ( 48 ), lung cancer ( 49 ), breast cancer ( 50 ), Burkitt’s lymphoma ( 51 ), and non-Hodgkin’s Lymphoma ( 52 ) as well as that patients with tumors expressing high levels of FLIP tend to have a poorer prognosis ( 53 , 54 ). However, c-FLIP performs also unexpected functions during cancer progression.…”
Section: Cellular Flice (Fadd-like Il-1β-converting Enzyme)-inhibitormentioning
confidence: 99%